The antioxidant activity and induction of apoptotic cell death by Musa paradisiaca and Trigona sp. honey jelly in ORL115 and ORL188 cells - Anuar, Mohd Nur Nasyriq; Ibrahim, Muhammad; Zakaria, Nor Hafizah; Ichwan, Solachuddin Jauhari Arief; Md. Isa, Muhammad Lokman; Mat Alewi, Nur Aizura; Hagar, Abdullah; Abdul Majid, Fadzilah Adibah (Penerbit Universiti Sains Malaysia, 2023)
Background: Head and neck cancer patients usually need nutritional support due to difficulties in swallowing and chewing. Therefore, this study aimed to formulate Musa paradisiaca and Trigona sp. honey jelly (MTJ) as a convenient functional food. Methods: The antioxidant properties were analysed using 2,2′-diphenyl-1 picrylhydrazyl (DPPH), ferric reducing antioxidant potential (FRAP) and 2,2′-azinodi 3-ethylbenthiazolinesulfonate (ABTS) assays. Cytotoxicity was assayed using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) test and the induction of apoptosis was observed via caspase-3/7 activity assay. The identification of phenolic compounds was done via ultra-high-performance-liquid chromatography coupled to mass spectrometer (UHPLC-MS/MS). Results: The antioxidant analysis exhibited: the half inhibitory concentration (IC50) of DPPH inhibition, 54.10 (SD = 4.51) µg/mL; the FRAP value, 30.07 (SD = 0.93) mM TEQ/100 g; and the ABTS value, 131.79 (SD = 8.73) mg TEQ/100 g. Cinnamic acid was the most abundant phenolic compound, followed by maleic acid and salicylic acid. The IC50 for ORL115 and ORL188 were 35.51 mg/mL and 43.54 mg/mL, respectively. The cells became rounded and dissymmetrical which reduced in number and size. The apoptotic cell death in ORL115 and ORL188 was deduced as caspase-3/7 activities that significantly increased (P < 0.05). Conclusion: The study evidenced that the antioxidant activity of MTJ could influence the induction of apoptosis in ORL115 and ORL188 in future investigations and verifications.